THE PRINCIPLE OF THE MAXIMUM AVAILABLE RESOURCES (MAR) OBLIGATION IN REGIONAL FINANCE IN INDONESIA - Ansar, Ansar; Razak, Abdul (Tadulako Law Review, 2020)
One of the major resources in the regions is financial resources sourced from the Regional Revenue and Expenditure Budget (APBD). In its management, it creates uncertainty about the fulfillment of human rights in regional financial management. This is because one of them is the regional financial regulation which causes the budget allocation for the issue of Economic, Social and Cultural Rights to be very inadequate. Therefore, this paper proposes that the government applies the Principle of Maximum of Available Resources (MAR) in the management of regional finances, especially in the budget for fulfillment of economic, social and cultural rights. In this research, the author uses a normative legal methodology by examining several regional financial law products (regional regulations on regional revenue and expenditure budgets) by utilizing two approaches, namely the statutory approach and the conceptual approach. In this research, the author limits it only to the right to social and cultural affairs in particular, the right to education, the right to health, the right to food, the right to housing. To discuss this matter, the authors chose 4 areas as research objects, namely Province of Kepulauan Bangka Belitung, Province of South Kalimantan, Malang City, Denpasar City and Palu City.